Development of Nd-Doped CaWO4 Single Crystalline Scintillators Emitting Near-Infrared Light - Kai Okazaki; Daisuke Nakauchi; Hiroyuki Fukushima; Takumi Kato; Noriaki Kawaguchi; Takayuki Yanagida (Applied Sciences, 2022)
Nd-doped CaWO4 single crystals with dopant concentrations of 0.1, 0.5, and 1% were synthesized by the floating zone method. The transmission, photoluminescence, and scintillation properties were evaluated from ultraviolet to near-infrared (NIR) ranges. An emission peak due to transitions of the host was observed at 400 nm, and several sharp peaks originating from Nd3+ 4f–4f transitions were confirmed at 900, 1060, and 1300 nm. The quantum yields of 0.1, 0.5, and 1% Nd-doped samples were 70.7, 79.5, and 61.2%, respectively, when monitored, and excited wavelengths were 750–1500 nm and 590 nm. Decay times consistent with typical Nd3+ transitions were obtained when NIR ranges were monitored. Additionally, the energy transfer between the host and Nd3+ occurred according to the decay measurement. The relationship between X-ray irradiated dose rate and intensity in the range of NIR was investigated by combining the crystals with an InGaAs-photodiode. The lowest detectable dose rate retaining the linearity of the present crystals was 0.3–0.06 Gy/h.